Poor people's knowledge : promoting intellectual property in developing countries - Finger, J Michael, ed; Schuler, Philip (Trade and development series, 2004)
This book aims to expand the international discourse by: Calling attention to a broader range of knowledge that has commercial potential in developing countries. Bringing an economic dimension into the discussion of traditional knowledge, where legal analysis has thus far been at the forefront. Bringing out the incentives for and concerns of poor people-which may be different from those of corporate research, Northern nongovernmental organizations (NGOs), or already successful entertainment stars. Demonstrating that the best answer is sometimes a commercial one, for example, providing musicians basic training in small business management or reform of regulations that burden small businesses, rather than obtaining formal patent or copyright protection. Calling attention to the many income-earning (rather than the income-using) dimensions of culture-to dispel the notion that culture and commerce are necessarily in opposition. Bringing out instances in which more or less standard legal approaches have been effective as an antidote to the general sense of conflict between traditional knowledge and normal legal conceptions so as to identify the problems in which legal innovation-beyond diligent application-is really needed. Imbuing into the discourse a sense of the legal and commercial tasks needed to solve a developmental problem-away from " knowledge " as an isolated legal issue.